Anaesthesia for non-obstetric surgery in obstetric patients - G L Ravindra; Abhinava S Madamangalam; Shwetha Seetharamaiah (Indian Journal of Anaesthesia, 2018)
Anaesthesia for pregnant patients presenting for non-obstetric surgery needs a thorough understanding of the physiological changes and altered pharmacokinetics of pregnancy. Considering the effects of surgery and anaesthesia on the foetus, only essential and emergency surgeries are performed during pregnancy. Surgical procedures in second trimester have the advantage of better foetal outcome. The primary concerns of maternal and foetal safety are achieved by a focused multidisciplinary team-based approach with respect to the surgical condition. Meticulous attention to preoperative patient counselling, airway management, haemodynamic stability, and thromboprophylaxis are the key factors in anaesthetic management. Choice of anaesthesia or anaesthetic drugs has minimal impact on the foetus provided utero-placental perfusion and uterine relaxation are maintained. Foetal monitoring when feasible and when done by a trained person enables to diagnose and treat the factors responsible for foetal heart rate variability. Anaesthetic technique needs to be modified according to the type of surgery.